Spatial Analysis Techniques Using MyGeoffice®: - Negreiros, João Garrott Marques (Advances in Geospatial Technologies, 2018)

Web 2.0 Tool Recommendations for Teachers - Negreiros, Joao Garrott Marques; Lei, Weng Chi (International Journal of Innovation and Research in Educational Sciences, 2019)

Hydrological Risk Assessment at Praia, Cape Verde - Silva, Jose Lino; Negreiros, Joao Garrott Marques (International Journal of Environment, Agriculture and Biotechnology, 2017)
Hydrology modeling became a relevant topic for the Cidade da Praia, Cabo Verde, Africa, due to negative impact risk to local population and its assets. The modeling via Geographical Information Systems (GIS) can help the decision-making process of space occupation and characterization for this type of risk. Under the municipalities of Praia, the phenomenon of flash flood is common, causing soil erosion and landslide. This constitutes a risk for the local habitat, particularly in districts with a lack of strong human infrastructures. To simulate, analyze and generate risk maps using GIS to help this county governance authorities for decision-making, thus, becomes the main aim of this article.

Performance evaluation of Macao governmental web portal - Cordova, Vicente Jorge (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Re-conceptualising computer literacy teaching and learning using constructivist principles and peer-tutoring - Wong, Kin Ming (University of Saint Joseph, 2015)
Nowadays, many university students (in Macau) are required to attend computer literacy courses to develop their basic skill levels and knowledge as part of their literacy foundation requirements. To be effective, such courses, which are very staff intensive and require access to expensive equipment and software, necessitate high levels of individual teaching. Evidence gathered at two study sites during this research, strongly suggests that many students may not be benefiting sufficiently from their computer literacy courses. Teachers frequently complain about the weak IT skills of many course graduates. This research proposes an innovative model for designing and delivering computer literacy courses based on constructivist principles, using peer-tutoring and blended learning to increase cost effectiveness and to improve student outcomes. Central to the model being proposed is the training and deployment of former course graduates as peer instructors and assessors. Constructivist principles provide a conceptual framework to ensure that the curriculum content, teaching strategies, learning styles and assessment procedures are properly aligned and fully understood by both the instructors and students to achieve high quality learning outcomes. An action research approach was used during the pilot and trail phases of the research to monitor the implementation of the model and evaluate its effectiveness using mixed methods. The planned two–phase action evaluation used a questionnaire to investigate the effectiveness of knowledge and skill transfer to students, and tutors’ learning progress; in-depth semi-structured interviews were used to survey, interpret and evaluate students’ and tutors’ perceptions of the new teaching and learning approach. Most respondents had a Confucian Heritage Cultural Background. For the first time, the research provides new insights into ways in which Confucian Heritage Cultural factors, interact with constructive principles in developing peer-tutoring methods in a university setting inMacau, and more widely
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

Spatial modulation of the hydrological risk at Praia, Cape Verde - Silva, José Lino; Neves, Ana Cristina; Negreiros, João Garrott Marques (IOP Conference Series: Earth and Environmental Science, 2016)
Hydrology modeling became a relevant topic for the Cidade da Praia, Cabo Verde, Africa, due to negative impact risk to local population and its assets. The modeling via Geographical Information Systems (GIS) can help the decision-making process of space occupation and characterization for this type of risk. Under the municipalities of Praia, the phenomenon of flash flood is common, causing soil erosion and landslide. This constitutes a risk for the local habitat, particularly in districts with a lack of strong human infrastructures. To simulate, analyze and generate risk maps using GIS to help this county governance authorities for decision-making, thus, becomes the main aim of this article.

O segredo do sucesso escolar: contributo da web 2.0 - Baptista, Zélia Maria de Oliveira (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Improving Students' Reading Literacy with the Guided Use of a Digital Reading Platform in a Chinese Primary School - Norte, Patricia Alexandra D. C. (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Ensino-aprendizagem da matemática: que lugar a mitos? que lugar a Macau? - Oliveira, Maria de Fátima Andrade de (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

English as a foreign language: a comprehensive study on teacher's self-efficacy and its antecedents in Macao - Lam, Man Ieng; Malungu, Laurie Baker; Negreiros, João Garrott Marques (University of Saint Joseph, 2019)
As societies globalize, mastery of a second or multiple languages has become an important index to enhance interaction in the society. In that English is a is a widely used medium of communication globally for engagement in international business, commerce, science, technology and governance, the benefits of an efficacious English language teaching force to facilitate the English acquisition process of students in classrooms around the world is highly valued. For the purpose of this study, the English language teacher efficacy instrument (ELTEI) was adapted to the local context to measure the professional efficacy of the English as a foreign language (EFL) teacher participants. The objective of the research was to investigate the degree of relationship between antecedent conditions and specific teacher efficacy in Macao. A mixed-method approach in a sequential phase design was adopted to explore the efficacy of English language teachers serving Chinese medium schools in a non-English speaking region in Asia. Phase-one employed a qualitative approach to contextualize the measurement instrument and to ascertain important characteristics of the target population. Phase-two ensured a quantitative approach to yield understanding regarding the influence of key antecedent conditions on the efficacy of English language teachers in Macao. As evidenced through multiple linear regressions and structural equation modeling, openness, neuroticism, and perceived school support were significant predictors for teacher’s self-efficacy in English teaching. Recommendations for the school management to enhance and sustain the efficacy of EFL teachers in Macao were discussed
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

Implementation of item response theory to English grammar assessment to map students' understanding and to foster learning - Ho, U. Kei (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph